Triage for civil support : using military medical assets to respond to terrorist attacks - Cecchine, Gary (National Defense Research Institute and RAND Health, 2004)
Even before the events of September 11, 2001, threat assessments suggested that the United States should prepare to respond to terrorist attacks inside its borders. This monograph examines the use of military medical assets to support civil authorities in the aftermath of a chemical, biological, radiological, nuclear, or conventional high explosives attack inside the United States. In conducting this study, the authors focused on the following questions: Under what circumstances could military medical assets be requested? What sort of asset is likely to be requested? Are appropriate assets and related planning processes in place for civil support? What are the legal (and other) barriers to military support to civil authorities, and how can they be overcome, if necessary? In addition to a discussion of the applicable literature and laws, this monograph also includes historical case studies focusing on instances in which military medical assets were requested to assist civil authorities following natural disasters. It also includes a review of two exercises, based on postulated attacks, involving senior officials from local, state, and federal agencies-one involving a smallpox attack in Georgia and another involving a "dirty bomb" attack in California